Usability of the Surprise Question by Nurses and Patients' Families for Risk Stratification in Emergency Patients: A Prospective Cohort Study - Yi Liu RN, BSc; Dongze Li MD, PhD; Yu Jia MD, PhD; Jing Yu MBBS; Fanghui Li MBBS; Yongli Gao RN, BS; Yan Ma PhD; Zhi Wan MD; Zhi Zeng MD; Wei Zhang RN, BS (SAGE Publishing, 2023)
The Surprise Question is an effective tool to identify patients in need of palliative care. But it is unknown whether the Surprise Question can effectively predict adverse outcomes in Emergency patients. Therefor this study is to determine the utility of the modified Surprise Question for risk stratification in emergency patients. And assessed if the modified Surprise Question could be used by different healthcare personnel. Nurses and patients' families were asked to respond as "Yes" or "No" to the modified Surprise Question for each patient. The outcome was resuscitation unit admission. Logistic regression was used to determine covariant significantly associated with resuscitation unit admission. The area under the curve for the second Surprise Question response by nurses was 0.620, which improved to 0.704 when the responses of nurses and patients' families were in agreement. The clinical impression of nurses is a valuable tool to predict altered conditions for medium-acuity patients, and the diagnostic accuracy improves when responses of patients' families and nurses agreed. The clinical impression of nurses is a valuable tool to predict altered conditions for medium-acuity patients, and the diagnostic accuracy improves when responses of patients' families and nurses agreed.